A novel CD2 staining–based flow cytometric assay for assessment of natural killer cell cytotoxicity. Issue 12 (17th August 2020) - Zhang, Dan; Teng, Rui; Lv, Nan; Lei, Lei; Wang, Yanmeng; Williamson, Ramone A.; Chen, Ping; Gao, Peigen; O'Dwyer, Michael; Li, Ang; Hu, Jinsong
Abstract: Background: Assessing cytotoxicity is fundamental to studying natural killer (NK) cell function. Various radioactive and non‐radioactive cytotoxicity assays measuring target cell death have been developed. Among these methods, the most commonly used 51 Chromium‐release assay (CRA) and flow cytometry–based cytotoxicity assays (FCCs) are the major representatives. Nonetheless, several drawbacks, including dye leakage and the potential effects of prior labeling on cells, curb the broad applicability of the FCCs. Methods: Here, we report a rapid FCC for quantifying target cell death after co‐incubation with NK cells. In this assay, after 4 hours of NK cell‐target cell co‐incubation, fluorochrome‐conjugated CD2 antibody was used to identify NK cells, and SYTOX Green and Annexin V‐FITC were further used to detect target cell death in CD2‐negative population. In parallel, both CRA and FCC assay using CFSE/ 7‐AAD were performed to validate the reproducibility and replicability. Results: We observed that CD2 is exclusively positive on NK cells other than the most common hematological target tumor cells, such as K562, HL60, MOLM13, Raji, NCI‐H929, rpmi8226, MM.1S, and KMS11. Assessment of target cell death using the CD2‐based FCC shows a significantly higher percent specific lysis of the target cells compared to the standard CRA and the FCC assay using CFSE and 7‐AAD. Conclusions: We demonstrated that this CD2‐based FCC is a fast, simple, and reliable method for evaluating NK cell cytotoxicity. Abstract : A CD2 staining‐based flow cytometric assay for measuring natural killer cell cytotoxicity. After incubation of NK cells with target cells at different E:T ratios for 4 hours, fluorochrome‐conjugated CD2 antibody was used to identify NK cells, nucleic acid dye SYTOX Green and early apoptotic marker Annexin V were further used to detect target cell death in CD2‐negative population. Compared to 51 Chromium release assay and other traditional flow cytometric assays, this CD2 based flow cytometric cytotoxicity assay is highly sensitive and reliable, since there is no any interference before or during the incubation by labeling cells.